Mechanistic insights into efficient methylene blue adsorption by single-rod mangosteen peel waste composite starch cryogel: Batch and column studies - Kharittha Phatthanawiwat; Chanadda Phawachalotorn; Worawit Wongniramaikul; Aree Choodum (Materials Today Communications, 2026)
A green composite tablet, based on the immobilization of mangosteen peel (MP) waste particles in starch cryogel (Cry-DMP), was successfully prepared and characterized. Cry-DMP exhibited a high adsorption capacity for methylene blue (MB), with a maximum capacity (qₘₐₓ) of 26.53 mg g⁻¹, and the equilibrium data were best described by the Langmuir model ( R² = 0.9902). High removal efficiencies of 97.21% in synthetic water and 70.8% in real Batik industrial wastewater were achieved without chemical activation of the mangosteen peel particles, demonstrating the practical applicability of the adsorbent. The suggested adsorption mechanism mainly relies on electrostatic interaction with additional contributions from hydrogen bonding and π–π interactions. The pseudo-second-order model best described the adsorption kinetics ( R² = 1), and the adsorption of MB onto Cry-DMP was determined to be spontaneous and endothermic. Furthermore, the Yoon–Nelson model accurately described the experimental results from continuous flow experiments ( R 2 = 0.8598 to 0.9981). Sodium silicate reduces removal efficiency by 8.82%, while sodium phosphate increases it by 2.94%. Cry-DMP effectively removes MB and other cationic dyes but is ineffective against anionic dyes, highlighting its selective adsorption capabilities. These findings emphasize the effectiveness of Cry-DMP as a green adsorbent for MB and highlight the feasibility of waste utilization with a greener approach. • A novel green adsorbent (Cry-DMP) was created from mangosteen peel waste and starch cryogel. • No activation of mangosteen peel particles is needed before preparing Cry-DMP. • Methylene blue was removed by 97.21% in synthetic water and 70.8% in real wastewater. • Cry-DMP effectively removes MB and other cationic dyes but fails to remove anionic dyes. • 100% weight loss of the sensors were achieved after soil burial for 15 days.
Keywords: Adsorption and biosorption for pollutant removal; Coagulation and Flocculation Studies; Phosphorus and nutrient management